2015
DOI: 10.1002/cpe.3442
|View full text |Cite
|
Sign up to set email alerts
|

Appearance, motion, and embodiment: unpacking avatars by fine‐grained communication analysis

Abstract: SUMMARYThanks to the maturity of motion tracking technologies, it became easy and inexpensive to use avatars that reflect the user's facial and body motions in real time. There is a possibility that those real-time avatars can serve as a substitute for videos in distant communication. We conducted two experiments to confirm positive effects of avatars on distant communication. In the first experiment, the subjects watched a conversation partner's video, avatar, photo, or nothing when speaking to the partner. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Although the transmitting appearance enhances social telepresence as mentioned above, it has not been clarified whether the appearance works even if the motion is not transmitted. The effect of presenting appearance on the smoothness of speech had already demonstrated (Tanaka et al, 2013(Tanaka et al, , 2015. The previous study showed that presenting partner's avatar increased the degree of the smoothness of speaking to the partner, but partner's photo did not have such an effect.…”
Section: Discussionmentioning
confidence: 96%
“…Although the transmitting appearance enhances social telepresence as mentioned above, it has not been clarified whether the appearance works even if the motion is not transmitted. The effect of presenting appearance on the smoothness of speech had already demonstrated (Tanaka et al, 2013(Tanaka et al, , 2015. The previous study showed that presenting partner's avatar increased the degree of the smoothness of speaking to the partner, but partner's photo did not have such an effect.…”
Section: Discussionmentioning
confidence: 96%
“…Avatar will increase a degree of smoothness of speaking to partner, though the appearance of the avatar itself will not affect much [14]. Facial expressions will improve the effectiveness of avatars in various contexts [4].…”
Section: Avatarmentioning
confidence: 98%
“…Tanaka et al . study the effects real‐time avatars had on distant communications when the avatars served as a substitute for videos in distributed environments. The paper discusses two experiments involving videos, photos, or avatars to supplement voice communications.…”
Section: This Special Issuementioning
confidence: 99%